Does it speak to me? Visual aesthetics and the digital divide. - Barbatsis, Gretchen; Camacho, Melissa; Jackson, Linda (Visual Studies, 2004)
New media research suggests a significant disconnect between the life experience of minorities and the content, information and services they find available with an Internet experience. The HomeNetToo project was a three-year study that focused on understanding how communities of people on the 'other side' of this digital divide make sense of the Internet when access is introduced into their homes. Guided by Brenda Dervin's (1989) sense-making framework, the research looked at the Internet as a social practice and sought to identify strategies with which these communities engaged and integrated this cultural form. Ethnographic interviewing and observations in respondent's homes allowed access to meanings within the experience of their everyday lives. As a whole, findings lend support to the notion that the digital divide is more a design issue than it is a socio-economic phenomenon and they provide avenues to pursue for improving the cultural diversity of interface design. The patterns reported here focus on issues of interest to visual communication research and visual design.